2021
DOI: 10.1101/2021.03.13.21249938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significance testing for small annotations in stratified LD-Score regression

Abstract: S-LDSC is a widely used heritability enrichment method that has helped gain biological insights into numerous complex traits. It has primarily been used to analyze large annotations that contain approximately 0.5% of SNPs or more. Here, we show in simulation that, when applied to small annotations, the block jackknife-based significance testing used in S-LDSC does not always control type 1 error. We show that the inflation of type 1 error for small annotations is due both to the noisiness of the jackknife esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Finally, stratified LD score regression has elevated false positive rates for small annotations, which may affect our analysis of small gene sets. 31 Despite these limitations, this study presents a novel approach for estimating gene-mediated heritability and informs our understanding of the convergence of common and rare genetic variation. Finally, we have released software for implementing AMM at the command-line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, stratified LD score regression has elevated false positive rates for small annotations, which may affect our analysis of small gene sets. 31 Despite these limitations, this study presents a novel approach for estimating gene-mediated heritability and informs our understanding of the convergence of common and rare genetic variation. Finally, we have released software for implementing AMM at the command-line.…”
Section: Discussionmentioning
confidence: 99%
“…There was a surprising 8.6x enrichment (SE: 2.7x, P = 2.3e-3) of neuroticism in the diabetes gene set; other brain-related traits were not enriched in this gene set (Supplementary Table 6), and S-LDSC is known to occasionally produce false positives for small annotations (see Discussion). 31 Finally, we analyzed mediated heritability enrichment in 251 genes associated with developmental disorders (mostly neurodevelopmental). We find enrichments for cognitive traits in this gene set, including schizophrenia (3.5x, P = 0.01) and neuroticism (3.5x, P = 0.01).…”
Section: Figure 3 | Snp-to-gene Architecture Of 47 Complex Traits (A)mentioning
confidence: 99%
“…First, we mapped proteins from the mouse proteome to their corresponding genes using Uniprot Knowledgebase (https:// www.uniprot.org/id-mapping) and converted the mouse genes to their human orthologs using the NCBI HomoloGene database. S-LDSC had primarily been used to analyze enrichment of large gene sets and it was shown that a Type I error is not always controlled in the analysis of small annotations or gene sets 65 . Therefore, we defined two protein sets of the top 1,000 upregulated and 1,000 downregulated proteins in each PSD proteome.…”
Section: Volumetric Brain Mrimentioning
confidence: 99%
“…Results are shown in table S4, with statistical significance defined as P adj < 0.05. Analyses were performed on both brain-filtered pelvic subelement sets and the smaller specific pelvic subelement sets, although, given issues of sparsity, the results of the latter were not considered reliable (64).…”
Section: Gwas Phenotypic Analysismentioning
confidence: 99%